Union catalog on Philippine culture visual arts and architecture. - Cultural Center of the Philippines. Library (Manila The Library, 1991)
A union catalog of 69 libraries, mostly academic, it is arranged into two parts: visual arts and architecture. Each section is further divided into monographs, thesis, analytics, periodical articles, an author-title-series index, and a subject index. Entries are arranged numerically, then alphabetically. Each entry is in card catalog format, with a control number and library code. The indexes use the control number to locate entries, instead of page numbers.
Keywords: Art -- Union lists. -- Philippines -- Bibliography; Architecture -- Union lists. -- Philippines -- Bibliography; Popular culture -- Union lists. -- Philippines -- Bibliography